Nidotherapy compared with enhanced care programme approach training for adults with aggressive challenging behaviour and intellectual disability (NIDABID): cluster‐randomised controlled trial. Issue 6 (26th January 2017) - Tyrer, P.; Tarabi, S. A.; Bassett, P.; Liedtka, N.; Hall, R.; Nagar, J.; Imrie, A.; Tyrer, H.
Abstract: Background: Aggressive challenging behaviour is very common in care homes for people with intellectual disability, and better psychological treatments are needed. Nidotherapy aims to change the environment of people with mental illness and is an appropriate treatment for this group of disorders. Method: The design was a cluster randomised trial of 20 care homes in which the staff either received training in nidotherapy or the enhanced care programme approach (ECPA), with equivalent duration of treatment in each arm. Cluster randomisation of care homes was carried out at the beginning of the study by an independent statistician. Primary and secondary outcomes were not specified exactly in view of absence of previous study data, but changes over time in scores on two scales, the Modified Overt Aggression Scale and the Problem Behaviour Check List were the main outcome measures. Serious violent incidents were recorded using the Quantification of Violence Scale. All these measures were recorded monthly by research assistants who were carefully kept blind to the allocation of treatment. Results: A total of 200 residents entered the trial, 115 allocated to the ECPA arm and 85 to the nidotherapy one. Seven residents left the care homes in the course of the study, and six were replaced; these were included 79 in the analysis as the trial was a pragmatic one. There were no material reductions in challenging behaviour in the first 8 months of the trial in either group, but in the last 7 months, those allocated to nidotherapy had a 33% reduction in Modified Overt Aggression Scale (MOAS) scores and a 43% reduction in Problem Behaviour Check List scores compared with 5% and 13%, respectively, for the ECPA group, differences which for the MOAS were close to statistical significance. Discussion: Nidotherapy shows promise in the management of aggressive challenging behaviour in care homes, but a delay in its benefit might be expected if given to staff only. The treatment is worthy of further evaluation and development.